BIOELECTRIC POTENTIAL MEASUREMENT DEVICE - NIIJIMA ARINOBU; MIZUNO OSAMU; TSUNODA KEISUKE; EGUCHI KANA (2016)
PROBLEM TO BE SOLVED: To provide a device in which biological information measurement can be easily performed by a user with no medical perspective regardless of a physique of a subject.SOLUTION: Bioelectric potential measurement devices 1A, 1B comprise device fixing parts 11 for fixing the bioelectric potential measurement devices 1A, 1B to a subject, and a plurality of surface myoelectric measurement parts 12A-12C based on distribution of muscles of a measurement object. This configuration enables a user with no medical perspective to measure surface myoelectric signals properly regardless of the physique of the subject without the need for confirming a muscle belly position of a muscle to be measured in advance.SELECTED DRAWING: Figure 1 【課題】被計測者の体格を問わず、医学的知見を持たなくても容易に生体情報計測を行うことができる装置を提供する。【解決手段】生体電位計測装置１Ａ，１Ｂが被計測者に生体電位計測装置１Ａ，１Ｂを固定する装置固定部１１と、計測対象の筋肉の分布に基づいた複数の表面筋電計測部１２Ａ〜１２Ｃを備える。これにより、被計測者は、体格を問わず、事前に計測対象の筋肉の筋腹位置を確認する必要がなく、医学的知見を持たないものであっても適切に表面筋電を計測することが可能となる。【選択図】図１